Hypothyroidism and Cognitive Disorders during Development and Adulthood: Implications in the Central Nervous System - Salazar, Paulina; Cisternas, Pedro; Martinez, Milka; Inestrosa, Nibaldo C. (My University, 2019)
Thyroid hormones (THs) play a critical function in fundamental signaling of the body regulating process such as metabolism of glucose and lipids, cell maturation and proliferation, and neurogenesis, to name just a few. THs trigger biological effects both by directly affecting gene expression through the interaction with nuclear receptors (genomic effects) and by activating protein kinases and/or ion channels (short-term effects). For years, a close relationship between the THs hormones and the central nervous system (CNS) has been described, not only for neuronal cells but also for glial development and differentiation. A deficit in thyroid hormones triiodothyronine (T-3) and thyroxine (T-4) is observed in the hypothyroid condition, generated by a iodine deficiency or an autoimmune response of the body. In the hypothyroid condition, several cellular deregulation and alterations have been described in dendrite spine morphology, cell migration and proliferation, and impaired synaptic transmission in the hippocampus, among others. The aim of this review is to describe the role of the thyroid hormones with focus in brain function and neurodegenerative disorders.
Keywords: thyroid hormones; brain function; neurodegenerative disease